Some thoughts on the Goldbach’s Conjecture (Part II) - D’AMICO, Rosario (Journal of Mathematical Economics and Finance; Vol 4 No 2 (2018): JMEF, Volume IV, Issue 2(7), Winter 2018, 2018)
This work aims at formulating considerations to demonstrate the Goldbach's Conjecture by using a demonstration process by far easier than the usual attempts already present in literature.